Detection of ureaplasmas and bacterial vaginosis associated bacteria and their association with non-gonococcal urethritis in men - Frølund, Maria (PLoS One, 2019)
No aetiology is found in up to 40% of men with symptomatic urethritis. Male partners of women with bacterial vaginosis (BV) may be at higher risk of non-gonococcal urethritis (NGU). The aim of this study was to examine the role of BV associated bacteria in first-void urine (FVU) in 97 asymptomatic men without urethritis (controls) and 44 men (cases) with NGU including 20 men with idiopathic urethritis (IU) attending a Swedish STD-clinic between January and October 2010. BV-associated bacteria and ureaplasmas were detected by quantitative PCR assays. All BV associated bacteria, except Megasphaera-like type 1, were strongly positively correlated with U. urealyticum p<0.005 and even stronger with the combined U. urealyticum and U. parvum load (p<0.0005) suggesting that ureaplasma induced elevated pH may stimulate the growth of BV associated bacteria. No statistically significant differences were found between IU cases and controls in the prevalence or load of BV associated bacteria or ureaplasmas. In multiple logistic regression, Megasphaera-like type 1 was associated with IU (p = 0.03), but most positive FVU samples contained very few bacteria and the finding may not be clinically relevant.